Збагачення виховного аспекту навчальних програм як засіб розвитку аксіологічного потенціалу студентів - Слесик, К. М. (НТУ "ХПІ", 2016)
Розглядається проблема аксіологізації вищої освіти в контексті виконання Закону "Про освіту" та інтеграції в європейську і світову освітню систему. Обґрунтовуються причини вказаного напряму наукових досліджень. Пропонуються шляхи активізації аксіологічного потенціалу студентів, один з яких полягає у збагаченні виховного аспекту змісту освіти на основі впровадження спеціально розроблених модулів аксіологічної спрямованості. Виховання ціннісної свідомості особистості студентів передбачає розширення поля виховного впливу через залучення студентів до самопізнання і саморозвитку.

Considers the problem of axiological of higher education in the context of the implementation of the Law "On education" and integration into European and world educational system. Reasons of the indicated direction of scientific researches are grounded. Ways of activation and the enrichment of the axiological potential of students was offered. One of them is to enrich the educational aspect of the content education through the introduction specially designed modules axiological orientation. Fostering value consciousness of individual students involves the expansion of the field educational influence, through the involvement of students in self-knowledge and self-development.
The enrichment of the educational aspect of the curriculum as a means of development axiological students` potential
Keywords: вища освіта; аксіологізація освіти; інсталяція змістового модулю; higher education; axiological education; installation of module